ANALISIS YURIDIS TERHADAP KERUSAKAN LINGKUNGAN AKIBAT AKTIVITAS PENAMBANGAN PASIR DI SUNGAI SERAYU KABUPATEN BANYUMAS DALAM PERSPEKTIF HUKUM SUMBER DAYA ALAM - Ati Setyowati; Eti Mul Erowati; Wiwin Muchtar Wiyono; Elly Kristiani Purwendah (Ganesha Law Review, 2026)
Sand mining activities in the Serayu River, Banyumas Regency, in recent years have caused various environmental impacts, including river ecosystem degradation, riverbank erosion, sedimentation, and declining environmental quality for surrounding communities. These problems indicate an imbalance between natural resource utilization and environmental protection. This study aims to analyze the legal regulations governing sand mining activities and to examine law enforcement related to environmental damage caused by such activities. The research method used is normative juridical research with statutory and conceptual approaches. Legal materials were obtained from legislation, journals, books, and other legal sources relevant to natural resource law and environmental law. The results of the study indicate that sand mining activities in the Serayu River still lead to various violations of environmental management provisions, particularly concerning licensing, supervision, and environmental protection obligations. Law enforcement against mining actors causing environmental damage is considered ineffective due to weak supervision and low compliance with existing regulations. Therefore, stronger government supervision and more effective law enforcement are necessary to preserve environmental sustainability and ensure the sustainable management of natural resources in the Serayu River, Banyumas Regency.